Penetrating The Boundary Of Minahasa Women In The Heritage Of Faith And The Dynamics Of Social Change - Manua, Englin Rahelia; Weol, Wolter; Pinontoan, Denni (International Journal of Education, Information Technology, and Others, 2025)
This study examines the role of Minahasa women in maintaining the heritage of the Christian faith in the midst of the dynamics of social, cultural, and economic changes triggered by the influence of colonialism and modernization. The urgency of the research arises from the need to understand how Minahasa women, who are agents of social transformation and guardians of traditional values, are able to adapt their roles in the face of the dual challenge between local cultural values and the demands of modern times. This research uses a literature review method with a qualitative approach, integrating theological hermeneutic analysis and historical sociological analysis to dive into women's perceptions, experiences, and contributions in religious and social contexts. The results of the study show that despite facing economic pressures, patriarchal systems, and changes in social structure, Minahasa women have managed to utilize education and Christian values as a means of empowerment. These findings affirm the strategic role of women in preserving traditions, developing social innovations, and leading transformation towards a more inclusive and equitable society.